Aplikasi biochar cangkang kernel kelapa sawit dan limbah baglog jamur terhadap pertumbuhan dan produksi padi beras merah pada pertanaman karet - Jason Hasibuan; Ellen Lumisar Panggabean; Sumihar Hutapea (Universitas Medan Area, 2019)
This research was aiming to find out whether the application of biochar palm kernel shell and mushroom baglog waste. The research was conducted by using the Factorial Randomized Group Design (RAK) with 2 treatment factors. The first factor was the biochar of the palm kernel shell and The second factor was the mushroom baglog waste which. The result of this research showed that the treatment of giving biochar to brown rice in rubber plantation had a real effect on the growth of the plant height in the age of 6 MSPT and the weight of production of sample crop and didn’t have a real effect on the production weight per plot, number of tillers, number of panicles of sample crop and the amount of 1000 grains of brown rice. The treatment of giving oyster mushroom baglog tp brown rice in rubber plantation had a real effect on the production of the rice per plot, and the production weight of sample crop and didn’t have a real effect on the growth of the number of the tillers, number of panicles of sample crops, and amount of 1000 grains of brown rice. The combination of both factors didn’t have a real effect on the growth and the production of brown rice.